The Modulation of Chaihu Shugan Formula on Microbiota Composition in the Simulator of the Human Intestinal Microbial Ecosystem Technology Platform and its Influence on Gut Barrier and Intestinal Immunity in Caco-2/THP1-Blue™ Cell Co-Culture Model - Liu, Ling; Lu, Yi; Xu, Chao; Chen, Haitao; Wang, Xuanying; Wang, Yijie; Cai, Biyu; Li, Bing; Verstrepen, Lynn; Ghyselinck, Jonas; Marzorati, Massimo; Yao, Qinghua (Frontiers in Pharmacology, 2022)
The traditional Chinese medicine (TCM) - Chaihu Shugan Formula (CSF), consisting of several Chinese botanical drugs like Bupleurum, is derived from the ancient Chinese pharmacopeia. It has been used for more than thousands of years in various suboptimal health statuses and diseases induced by chronic stress based on empirical therapy. Recent studies confirm the role of CSF in the development of many diseases, including depression, stress-induced hepatic injury and tumors. However, little has been known about the mechanisms behind the health effects of CSF. Here, we investigate the influence of CSF on the modulation of the simulated colonic microbiota of five healthy donors, gut barrier integrity, and intestinal immunity by combining the simulator of the human intestinal microbial ecosystem (SHIME®) technology platform with co-culture of intestinal and immune cells. This approach revealed that CSF stimulated the production of SCFA (acetate, propionate and butyrate) across donors while significantly lowering the production of branched SCFA (bSCFA). In terms of community composition, CSF stimulated a broad spectrum of health-related Bifidobacterium species, which are potent acetate and lactate producers. At the same time, it lowered the abundance of opportunistic pathogenic Escherichia coli. Later, we explore the effect of colonic fermentation of CSF on the gut barrier and intestinal immunity in the Caco-2/THP1-blue™ cell co-culture model. Based on the study using SHIME technology platform, CSF showed protective effects on inflammation-induced intestinal epithelial barrier disruption in all donors. Also, the treatment of CSF showed pronounced anti-inflammatory properties by strongly inducing anti-inflammatory cytokines IL-6 and IL-10 and reducing pro-inflammatory cytokine TNF-α. These findings demonstrate a significant modulatory effect of CSF on intestinal gut microbiota. CSF-microbial fermentation products improved the gut barrier and controlled intestinal inflammation.